Unique-Maximum Coloring Of Plane Graphs - Fabrici Igor (Discussiones Mathematicae Graph Theory, 2016)
A unique-maximum k-coloring with respect to faces of a plane graph G is a coloring with colors 1, . . . , k so that, for each face of G, the maximum color occurs exactly once on the vertices of α. We prove that any plane graph is unique-maximum 3-colorable and has a proper unique-maximum coloring with 6 colors.